A classe média na sociedade capitalista sob a análise do marxismo estruturalista - Brandelli, Danilo Martins (2019)
The Sociology has produced vast content about the middle class in specific analyzes cutting a historical period, or, regarding the middle unions, whether in income analyses or seeking a different status of the manual worker, but little has been produced so far. about clarifying the concept of middle class in sociology. Therefore, this research seeks to systematize the concepts of the middle class most used in sociology, which are Marxist and Weberian. To this end, the advances and limits of such concepts that culminate in a Marxist proposal of social classes about the middle class will be demonstrated. Structuralist Marxism failed to set aside the problems of the middle class that challenged them in the 1950s and 1970s in the face of the great commitment of non-Marxist researchers to elaborate a concept of the middle class in the face of the quantitative advance of non-manual / unproductive workers in societies. capitalists. Non-Marxist research, however, because it did not work with the concept of Marxist social classes, inserted the middle class as a class outside the contradiction between the main classes: the bourgeoisie and the working class, whose confrontation with this problem was made by the structuralist Marxism that proposed to include the middle class in the class struggle and dared to propose a middle class ideology that corresponded to their class practices, a concept that has been shown to be very operable in historical research by Saes (1984, 1985).